1963
DOI: 10.1071/ph630526
|View full text |Cite
|
Sign up to set email alerts
|

The Type IV Solar Radio Burst at Metre Wavelengths

Abstract: SummaryProperties of 24 sources of type IV emission at metre wavelengths (including the long-lived continuum storms) have been observed by interferometry in the frequency range 40-70 Mc/s and by dynamic spectroscopy in the frequency range 15-210 Mc/s. The characteristics investigated are the positions, movements, and angular sizes of the sources, and the spectrum and polarization of the emission.Two varieties of the metre-wave type IV burst with distinctive characteristics, notably in height and movement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…First studies suggested that moving Type IV bursts are emitted by synchrotron or gyro-synchrotron emitting electrons that are trapped inside CME loops (Boischot & Clavelier 1968;Dulk 1973). However, since their discovery, a number of stationary Type IV radio sources have been observed that are believed to be generated by the plasma emission mechanism (Weiss 1963;Benz & Tarnstrom 1976), while some moving Type IV bursts have also been identified as plasma emission (Gary et al 1985). Bastian et al (2001) were the first to report the existence of a radio CME, which was observed as an ensemble of loop structures imaged by the Nançay Radioheliograph.…”
Section: Introductionmentioning
confidence: 99%
“…First studies suggested that moving Type IV bursts are emitted by synchrotron or gyro-synchrotron emitting electrons that are trapped inside CME loops (Boischot & Clavelier 1968;Dulk 1973). However, since their discovery, a number of stationary Type IV radio sources have been observed that are believed to be generated by the plasma emission mechanism (Weiss 1963;Benz & Tarnstrom 1976), while some moving Type IV bursts have also been identified as plasma emission (Gary et al 1985). Bastian et al (2001) were the first to report the existence of a radio CME, which was observed as an ensemble of loop structures imaged by the Nançay Radioheliograph.…”
Section: Introductionmentioning
confidence: 99%
“…This radiation was firstly recognized at meter wavelengths by Boischot (1957) and referred to the type IV burst. Weiss (1963) initiated to distinguish type IV bursts in height and movement of burst's sources. Subsequently, due to the fact that the radio emission was often related to the continuum at decimeter and centimeter wavelengths with differentiation of various phases within each individual event, this gave rise to overabundance of type IV categories and sub-categories.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the type IV (t-IV) radio burst is the most likely type related to the eruptive flux rope structure, while the type I burst is related to active regions (ARs) often in the absence of strong solar activities, the type II burst is attributed to energetic electrons accelerated at coronal shocks (see Feng et al 2013Feng et al , 2015Kong et al 2012;Chen et al 2014;Vasanth et al 2014;Du et al 2015 for latest studies), and type III and V bursts are given by energetic electrons accelerated at solar flares propagating outward along open field lines. The t-IV bursts are broadband continuum emission, further classified as the moving t-IV (t-IVm) and static t-IV bursts (Weiss 1963;Melrose, 1980), generally believed to be excited by energetic electrons trapped within certain magnetic structures, such as magnetic arches, loops, or plasmoid structures (Smerd & Dulk 1971;Vlahos et al 1982;Stewart 1985). Different emitting mechanisms have been proposed, including the synchrotron and gyro-synchrotron emission (Boischot 1957;Bastian & Gray 1997;Bastian et al 2001), the plasma emission (Duncan 1981;Stewart 1982;Ramesh et al 2013), and the electron cyclotron maser emission (Kujipers 1975;Lakhina & Buti 1985;Winglee & Dulk 1986).…”
Section: Introductionmentioning
confidence: 99%